State and society in eighteenth-century France a study in political power and popular revolution in Languedoc - Miller, Stephen Jacobus 1968- (Brill, 2023)
"In contrast to the traditional Marxist interpretation of emerging capitalism and a revolutionary bourgeoisie, this book shows that commodified labor, fundamental to the existence of a capitalist bourgeoisie, did not take shape in eighteenth-century France. The mass of the population consisted of peasants and artisans in possession of land and workshops, and embedded in autonomous communities. The old regime bourgeoisie and nobility thus developed within the absolutist state in order to have the political means to impose feudal forms of exploitation on the people. These class relations explain the crisis of 1789 and the revolutionary conflicts of the 1790s"--
Keywords: Geschichte 1700-1800; Bürgertum; Adel; Soziale Situation; Languedoc; Frankreich; Languedoc (France) / Politics and government / 18th century; Languedoc (France) / Social conditions / 18th century; Languedoc (France) / History / 18th century; Nobility / France / Languedoc / History / 18th century; Nobility; Politics and government; Social conditions; France / Languedoc; 1700-1799; History